Effect of polymer nanoparticle morphology on fracture toughness enhancement of carbon fiber reinforced epoxy composites. (1st April 2022) - Ning, Na; Wang, Ming; Zhou, Gang; Qiu, Yiping; Wei, Yi
Abstract: Poor interlaminar fracture toughness has been a major issue in carbon fiber reinforced thermoset polymer composites. A number of techniques have been studied to improve this property, and resin matrix modification is the most direct and effective one. This study focuses on nanoparticle (NP) toughening of epoxy resins and how well the matrix toughness improvement transfers to its carbon fiber reinforced composites. The NPs used contain the same percentage of soft and hard polymer composition, but have different particle morphology, i.e. homogenous versus core/shell structures. Results show that the core/shell particles, especially when the soft polymer is the core and the rigid polymer is the shell, give 851%, 185%, and 43% enhancement in G IC (epoxy), G IC (composite) and G IIC (composite), respectively, compared to the control specimen. Homogeneous particles are much less effective. Fracture surface morphology analysis suggests that effective toughening of composite requires the combination of well dispersed and strong particle-resin and resin matrix-fiber interfaces. This study provides insightful guidelines in selecting high-efficiency toughening particles, as well as comprehensive data on toughness transfer from neat resin to its corresponding composites.